Implementation of Basic Motion Learning and Use of Test Instrument of Gross Motor Development (TGMD) in Evaluating Basic Motion Skills - Oktarifaldi - Oktarifaldi; Risky Syahputra; Hasriwandi Nur; Willadi Rasyid; Sari Mariati (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2019)
UNESCO reports that the implementation of PAUD in Indonesia places great importance on academic content such as writing, arithmetic and reading and provides very little opportunity to actively play physically with children. Research shows that physical activity of children at an early age will greatly trigger the development of cognitive abilities. Based on observations and studies in the field, it was found that almost all teachers and educators in PAUD Sijunjung district did not have the insight and skills in measuring and evaluating the basic movements of children. Based on research, basic motion cannot develop naturally but must be taught correctly and continuously. This community service activity for partners aims to: (a) find out the importance of basic motion, (b) have skills in practicing basic early childhood movements, (c) be able to use instruments to measure basic movement skills in early childhood. The method used uses the principle that every innovation received by PAUD teachers through PIE (Preparation, Implementation and Evaluation). This means that the delivery of innovations to Partners is carried out through the stages of explanation, discussion, practice as well as the evaluation phase with assistance in the learning process. The results of the training obtained by partners as participants can be described as follows: (a) Having insight and understanding of the importance of basic movement skills, (b) having experience in practicing basic motion skills, (c) knowing and having the ability to use basic motion skills test instruments.